Young people’s drug consumption viewed in the light of their mental well-being and relationship with parents - Guðjohnsen, Ragný Þóra; Arnarsson, Ársæll (Menntavísindasvið Háskóla Íslands, 2022)
During adolescence, individuals face various changes and challenges. Parents tend to become insecure in the parenting role during these years. Concerns have been directed at how their children will fare in the coming years and in the future. Some caregivers strive to prepare them as best they can, fostering their well-being, communication skills, and health. Others experience challenges in their upbringing, feeling that they are losing control and unable to steer the child in the right direction. This is not without reason. The period of adolescence increases young people’s vulnerability to mental health problems as many mental illnesses appear during these years. Mental well-being is the prerequisite for people’s prosperity both as individuals as well as citizens where everyone’s ingenuity and skills should be recognized. It is, therefore, worrying that mental stability is deteriorating among young people in the Western world. Mental health policy has been called on as well as different resources and treatments and already many nations have placed mental health at the center of their agendas. In adolescence experiments with substances are also common. In Iceland adolescent binge drinking was strikingly common in the 70s, 80s and 90s but with joint preventive efforts of parents, schools, and authorities there has been a positive trend in the direction of much less alcohol being used by teenagers in junior high school. However, as teenagers get older, substance use rises, both in frequency as well as quantity, with increasing variety of substance types. Since the 80s there has also been constant growth in adult alcohol consumption in Iceland and young people aged 18–34, are among these consumers and the group at greatest risk for heavy drinking. Cannabis use among adolescents in Iceland is also on the rise, even in junior high school. In addition, young people are using more prescription drugs. All this is a matter of concern. Studies in Iceland have focused on different risk and protective factors, both related ...